2000
DOI: 10.15760/etd.2670
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Components: A Model for Enhancing Retrieval of Domain- Specific Information

Abstract: Semantic component searching allows a user to refine a topical search by indicating a preference for documents containing specific semantic components or by indicating terms that should appear in specific semantic components. 2We investigate four aspects of semantic components in this research. First, we describe lessons learned from using two methods for developing schemas in two domains. Second, we demonstrate use of semantic components to express domainspecific concepts and relationships by mapping a publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 115 publications
(128 reference statements)
0
7
0
Order By: Relevance
“…We found that the cost of manual semantic component indexing (with respect to time and intellectual effort) is similar to manual keyword indexing. We also found that the accuracy and consistency, while not directly comparable, appeared to be as good or better than that of keyword indexing [11]. In settings where manual keyword indexing is feasible, such as sundhed.dk, the quality level of semantic component indexing we used in this study is practical.…”
Section: Summary and Future Workmentioning
confidence: 77%
See 4 more Smart Citations
“…We found that the cost of manual semantic component indexing (with respect to time and intellectual effort) is similar to manual keyword indexing. We also found that the accuracy and consistency, while not directly comparable, appeared to be as good or better than that of keyword indexing [11]. In settings where manual keyword indexing is feasible, such as sundhed.dk, the quality level of semantic component indexing we used in this study is practical.…”
Section: Summary and Future Workmentioning
confidence: 77%
“…In other work [11], we discuss schema creation in more detail, comparing semantic component schemas to other indexing and classification structures, and discuss an alternative approach to schema creation that focuses primarily on the known purposes for the document collection and begins by identifying any existing document types or templates. In that work we also present data from an experiment that assesses indexing consistency when multiple indexers use a semantic component schema, similar to the one used in this study, to index a selection of documents from sundhed.dk.…”
Section: Effect Of the Semantic Component Schema On Searching Resultsmentioning
confidence: 99%
See 3 more Smart Citations